Exploring the Effects of Natural Capital Depletion and Natural Disasters on Happiness and Human Wellbeing: A Study in China - Lu, Fami; Sohail, Muhammad Tayyab (Frontiers in Psychology, 2022)
Since recent climate change has caused more natural disasters (NDs) than ever before, there is a worldwide concern that this could have both short-term and long-term economic and health consequences. This is perhaps the first attempt to explore the effects of natural capital (NC) and NDs on the human health and wellbeing of China over the period 1993–2020. The study has compiled data from World Bank, World Value Survey, UNDP, EM-DAT, and IMF for analysis. The empirical analysis is done by using the autoregressive distributed lag model. Empirical results prove that NC has a positive and significant effect on happiness, health, and human wellbeing in the long run. The results also show that NDs significantly reduce happiness and human wellbeing in the long run. The results recommend some important policy implications.